Comportamento mecânico e biológico de implante dentário com interface cônica interna - Castro, Carolina Guimarães (2015)
The general aim of this study was to evaluate the conical interface of pilar/implant. The specific aims were to evaluate the influence of hexagonal internal index in the microleakage and mechanical strength of Morse taper implants; the effect of axial loading on the deformation in cervical region of Morse taper implants of different diameters through strain gauge; the effect of axial loading in cervical deformation and sliding of abutment into the implant by tridimensional measurements; the integrity of conical interface before and after dynamic loading by microscopy and microleakage; and the stress distribution in tridimensional finite element models of Morse taper implants assembled with 2 pieces abutment. According to the obtained results, could be concluded that the diameter had influence in the cervical deformation of Morse taper implants; the presence of internal hexagonal index in the end of internal cone of implant didn´t influenced the bacterial microleakage under static loading neither reduced the mechanical strength of implants; one million cycles of vertical and off-center load had no negative influence in Morse taper implant integrity.